2008
DOI: 10.1200/jco.2008.17.3138
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Phase II Study of Vandetanib Alone or With Paclitaxel and Carboplatin as First-Line Treatment for Advanced Non–Small-Cell Lung Cancer

Abstract: VPC could be safely administered to patients with NSCLC, including those with squamous cell histology and treated brain metastases. Compared with the PC control arm, patients receiving VPC had longer PFS, meeting the prespecified study end point, whereas those receiving vandetanib monotherapy had shorter PFS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
153
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 216 publications
(159 citation statements)
references
References 26 publications
(2 reference statements)
3
153
0
3
Order By: Relevance
“…A meta‐analysis of 9 randomized trials with 4813 patients estimated a risk ratio for QTc prolongation versus control of 7.90 (95% confidence interval, 4.03–15.50) 154. In our review, the weighted incidence of any vandetanib‐related QTc prolongation was 8.6%, with QTc >500 ms in 2.6% 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70155, 156, 157 Because of its long half‐life (19 days), special care is needed when monitoring patients with QTc prolongation.…”
Section: Resultsmentioning
confidence: 75%
“…A meta‐analysis of 9 randomized trials with 4813 patients estimated a risk ratio for QTc prolongation versus control of 7.90 (95% confidence interval, 4.03–15.50) 154. In our review, the weighted incidence of any vandetanib‐related QTc prolongation was 8.6%, with QTc >500 ms in 2.6% 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70155, 156, 157 Because of its long half‐life (19 days), special care is needed when monitoring patients with QTc prolongation.…”
Section: Resultsmentioning
confidence: 75%
“…PFS was superior with docetaxel + vandetanib 100 mg/d versus docetaxel alone. In study 7, combining vandetanib 300 mg/d with carboplatin-paclitaxel produced a greater PFS benefit than carboplatin-paclitaxel alone (17). In this study, the vandetanib 300 mg/d monotherapy arm was inferior to carboplatin-paclitaxel alone.…”
mentioning
confidence: 62%
“…In studies 6 and 7, the addition of vandetanib 300 mg/d to docetaxel and carboplatin-paclitaxel, respectively, yielded modest PFS benefits compared with chemotherapy alone (HR, 0.83 and 0.76, respectively), and the greatest PFS benefit was seen when vandetanib 100 mg/d was added to docetaxel (HR, 0.64; refs. 16,17). As shown in four randomized phase III studies, the addition of EGFR TKIs to chemotherapy for NSCLC does not improve outcome (22)(23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the compound was also known to be a sub-micromolar inhibitor of epidermal growth factor receptor (EGFR) tyrosine kinase, the early preclinical evidence suggested that this activity is not essential for antitumour effects in vivo since vandetanib demonstrated significant inhibitory activity against a histologically diverse panel of human tumour xenografts, including models insensitive to gefitinib, a highly selective EGFR tyrosine kinase inhibitor (TKI) (1,3). In the clinic, vandetanib has shown activity in non-small cell lung cancer (NSCLC) both as monotherapy and in combination with chemotherapy (4)(5)(6). Vandetanib monotherapy has an acceptable safety and tolerability profile at doses of up to 300 mg/day, where the steady-state mean plasma drug concentration is approximately 1000 ng/ml (2.2 µM; range 1.6-6.3 µM), and where adverse events included hypertension, rash and diarrhoea (7,8) which is consistent with pharmacological inhibition of both VEGFR receptor-2 (VEGFR-2) and EGFR in normal tissues.…”
Section: Introductionmentioning
confidence: 99%